SOLVING SOME CHEMICAL PROBLEMS USING EQUATIONS - Khalilov Murodiljon Durbek Ugli (Bright Mind Publishing, 2026)
There are difficulties in calculating some chemical reactions, which make it easier to solve such reactions by making the equation appear. Sometimes we encourage students to solve problems using ready-made formulas in percentage concentration, and in other cases using proportions.
Keywords: percentage, concentration, proportion, weight, amount of substance, sulfur, percentage, oxide.